PERKEMBANGAN SILAT PANGEANDI KECAMATANPANGEAN KABUPATEN KUANTAN SINGINGI TAHUN 2010-2015 (Suatu Kajian Historis Terhadap Nilai-Nilai Budaya Lokal) - Supandri Supandri; Ridwan Melay; Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Silat Pangean has come up with a variety of style and toughnessconvincing and reflects a harmonious life, in addition to the virtuous piety is reflected inevery personal arts followers.Therefore Pangean has grown everywhere, not just in thearea of Riau, Jambi and Malaysia. The purpose of this study was to determine (1) theinterest Youth Silat Pangean (2) Structure of the Silat Pangean (3) What message iscontained in martial Pangean (4) Business and constraints in Preserving Silat Pangean inthe district of Pangean Kuantan. the method used is the qualitative and quantitativemethods. Engineering samples used in this study is purposive sampling techniques of dataanalysis in this research is descriptive qualitative. The results of this study are in line withthe passage of time and the development of science and technology and innovation in avariety of martial arts, and a variety of martial arts that is in the world Silat Pangean stillsurvive and exist in every person who has an interest and the interest in Silat PangeaniniKaum young participating in any martial arts event Pangean often held in the month ofRamadan more, almost all of the young people in the district following the event Pangeantersebut.Silat Pangean allowed to openly teach, a teacher of martial arts pages can be setup anywhere, these martial arts as long as the student of induak barompek it getspermission from the martial arts teacher Pangea and the area being laman.Silat Pangeanamong other areas, such as Pelalawan, Siak, even to Amerika.Silat PANGEAN veryattractive because in addition to the good life of peace and security both physical andspiritual. Silat has Pangean messages contained therein, in order to remain faithful toworship God Almighty.Keywords: development, Silat Pangean